Opsonisation and phagocytosis of group B meningococci by polymorphonuclear leucocytes: comparison of sulphonamide sensitive and resistant strains. - Ward, K N (1987)
A large proportion of disease caused by sulphonamide resistant strains of group B type 15 meningococci affects patients 10-24 years. In contrast, disease caused by sulphonamide sensitive strains conforms to the usual pattern, and most infection occurs in early childhood. In an attempt to explain this phenomenon possible differences in susceptibility of resistant and sensitive strains to phagocytosis by polymorphonuclear leucocytes were investigated, using radioactively labelled bacteria. In initial experiments a group B resistant strain required higher concentrations of normal human serum and longer opsonisation times for phagocytosis than an ungroupable non-pathogenic meningococcus. Comparison of sulphonamide resistant and sensitive group B meningococci showed that with either heat inactivated serum or agammaglobulinaemic serum, phagocytosis did not occur with any of the strains, whereas if these two sera were used together, phagocytosis was restored to the level seen with normal human serum. Thus both antibody and complement are required for phagocytosis. Furthermore, opsonisation depended on an intact classical pathway of complement for each group B strain. In all the experiments there was no significant difference between the phagocytosis of sulphonamide sensitive and resistant group B strains neither with regard to the efficiency of opsonisation by normal human serum nor the exact requirements for antibody and complement.